Rendimiento de cuatro variedades de fréjol (Phaseolus vulgaris L.) con aplicación de abonadura orgánica - Salas Bravo, Jennifer Fernanda (2011)
This research was performed at the "Envy", located at kilometer 20 of route Quevedo - Babahoyo, belonging to the Canton Mocache, province of Los Ríos. Its geographical location is of 01º 6' height and 79º 29' west longitude, the investigation lasted 65 days. 4 was tested bean varieties (Phaseolus vulgaris L), INIAP 472, INIAP 417, INIAP 414 and INIAP 404. The research had the following overall objective, evaluate the agronomic performance of four varieties of beans (Phaseolus vulgaris L) with organic and chemical abonadura (traditional, humus, compost and biological). The experimental design was randomized complete block (RCBD) with 4 replicates y16 treatments. To establish the difference between treatments was employed multiple range test of Tukey at 5% probability and the coefficient of variation is expressed in percentages. Variables were analyzed: germination, plant height at 8, 15, 30 and 45 days, days to flowering, flowers per plant, days to mature pods per plant, seeds per pod, grains per plant, grain yield kg plot , pod yield kg \ ha in grain and pod. This research demonstrated that organic fertilizers are needed to improve the pH and soil microbial conditions.